A dual mechanism for intrinsic f0. (July 2021) - Chen, Wei-Rong; Whalen, D.H.; Tiede, Mark K.
Highlights: The articulatory mechanism for intrinsic f0 (IF0) is still unclear. Articulatory data of 44 American English speakers was examined for correlates of IF0. The mandible was found to make contributions to IF0 independently of the tongue. A hypothesis for a dual mechanism for IF0 is supported. Abstract: Vowel-intrinsic fundamental frequency (IF0), the phenomenon that high vowels tend to have a higher fundamental frequency (f0) than low vowels, has been studied for over a century, but its causal mechanism is still controversial. The most commonly accepted "tongue-pull" hypothesis successfully explains the IF0 difference between high and low vowels but fails to account for gradient IF0 differences among low vowels. Moreover, previous studies that investigated the articulatory correlates of IF0 showed inconsistent results and did not appropriately distinguish between the tongue and the jaw. The current study used articulatory and acoustic data from two large corpora of American English (44 speakers in total) to examine the separate contributions of tongue and jaw height on IF0. Using data subsetting and stepwise linear regression, the results showed that both the jaw and tongue heights were positively correlated with vowel f0, but the contribution of the jaw to IF0 was greater than that of the tongue. These results support a dual mechanism hypothesis in which the tongue-pull mechanism contributes to raising f0 in non-low vowels while a secondary "jaw-push" mechanism plays a more important role in lowering f0 for non-high vowels.